2015
DOI: 10.1128/aem.01690-15
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evolution of Enhanced Growth by Bacillus subtilis at Low Atmospheric Pressure: Genomic Changes Revealed by Whole-Genome Sequencing

Abstract: Knowledge of how microorganisms respond and adapt to low-pressure (LP) environments is limited. Previously, Bacillus subtilis strain WN624 was grown at the near-inhibitory LP of 5 kPa for 1,000 generations and strain WN1106, which exhibited increased relative fitness at 5 kPa, was isolated. Genomic sequence differences between ancestral strain WN624 and LP-evolved strain WN1106 were identified using whole-genome sequencing. LP-evolved strain WN1106 carried amino acid-altering mutations in the coding sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Changes in colony morphology (110 generations) (Koeppel et al, 2013) Low pressure Increased fitness at low pressure (temperaturedependent) (Waters et al, 2015) High temperature More regular cell morphology near upper limit; altered membrane lipids; deregulated heat shock regulon (Zeigler, unpublished) we failed to find any mutation in the motility-specific sigma factor SigD (Brown et al, 2011;Maughan and Nicholson, 2011). We directly tested whether inactivation of these pleiotropic regulators indeed contributed to the increased fitness of WN716 by constructing in the ancestral strain WN624 insertional knockouts of the alsR, sigW, and sigD genes, singly and in combination.…”
Section: Liquid Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Changes in colony morphology (110 generations) (Koeppel et al, 2013) Low pressure Increased fitness at low pressure (temperaturedependent) (Waters et al, 2015) High temperature More regular cell morphology near upper limit; altered membrane lipids; deregulated heat shock regulon (Zeigler, unpublished) we failed to find any mutation in the motility-specific sigma factor SigD (Brown et al, 2011;Maughan and Nicholson, 2011). We directly tested whether inactivation of these pleiotropic regulators indeed contributed to the increased fitness of WN716 by constructing in the ancestral strain WN624 insertional knockouts of the alsR, sigW, and sigD genes, singly and in combination.…”
Section: Liquid Culturementioning
confidence: 99%
“…Strain WN1106, isolated from the 1000-generation culture, out-competed the ancestral strain at 5 kPa, but not at Earth-normal pressure. Genome sequencing detected only 8 mutations in WN1106: SNPs in the fliI, parC, resD, ytoI, yvlD, bacD and walK genes, and an in-frame, 9-nucleotide deletion in the rnjB gene, rnjBD9 (Waters et al, 2015). The rnjB gene encodes subunit RNase J2 of the RNA degradosome, an enzyme complex that governs global RNA turnover in B. subtilis (Cho, 2017).…”
Section: Evolution With Selection For Low-pressure Growthmentioning
confidence: 99%
“…Since all marine and surface environments are impacted by winds, the emanation/deposition of airborne microorganisms (hereafter referred to as bioaerosols) contributes to ecosystem dynamics. For instance, airborne microorganisms surviving harsh conditions while aloft, including strong levels of mutagenic ultraviolet radiation, might be altered at the genomic, transcriptomic, and proteomic level upon germination in a new environment (Smith et al, 2011 ; Chudobova et al, 2015 ; Waters et al, 2015 ; Khodadad et al, 2017 ). With hundreds of teragrams of microbe-laden dusts from deserts and agricultural soils moving through Earth's atmosphere each year (Acosta-Martinez et al, 2015 ), additional surveys are needed to better understand the ecological consequences of airborne biomass exchange, including disease dispersal (Brown and Hovmoller, 2002 ; Fröhlich-Nowoisky et al, 2016 ; Mahaffee and Stoll, 2016 ; Van Leuken et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of SNPs also reflects the variability within the cell population at genome sequence level, shows the regions of hypermutation in the genome where the mutations occur with an elevated frequency, and is suitable for the investigation of short-time evolution events (Brown et al 2011 ; Waters et al 2015 ). It has been suggested that the local hypermutation phenomenon in B. subtilis is in connection with the transcription-associated stationary-phase mutagenesis, which is in relation with the high expression level of the target gene and Mfd, the transcription repair coupling factor (Pybus et al 2010 ; Robleto et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%